Enhanced Th1/Th2 mixed immune responses elicited by polyethyleneimine adjuvanted influenza A (H7N9) antigen HA1-2 in chickens. (1st August 2018) - Song, Li; Xiong, Dan; Hu, Maozhi; Jiao, Xinan; Pan, Zhiming
ABSTRACT: Influenza A (H7N9) viruses have caused severe human infections and deaths every year in China since 2013. To reduce the risk of human infection and prevent a new influenza pandemic, there is a pressing need to develop safe and effective anti-H7N9 vaccines for poultry. Polyethyleneimine (PEI) is an organic polycation used extensively as a transfection reagent for decades. Although the adjuvant potential of PEI is well studied in mammals, its applicability and immune characteristics to avian species are still very rare. Here, to investigate the adjuvant activity of PEI, we analyzed the immune responses in chicken peripheral blood mononuclear cells in vitro. PEI significantly upregulated the expression of immune-related cytokines (IFN-γ, IL-2, IL-4, IL-6, IL-18, and IL-1β) and chemokines (CXCLi1, CXCLi2, MIP-1β, and MCP-3), suggesting that PEI promoted immune responses of avian cells. We also assessed the in vivo immune responses to PEI in a chicken model. After the second and third vaccinations, significantly higher IgG titers were observed in the chickens immunized with HA1-2+PEI than that of HA1-2 alone. The HA1-2+PEI group also increased percentages of CD4 + and CD8 + T cells and improved PBMC proliferation. The significantly upregulated IFN-γ and IL-4 levels of splenocytes from HA1-2+PEI vaccinated chickens further indicated that PEI promoted a Th1/Th2 mixed immune responses. This study not only demonstrates the adjuvant potential of PEI when co-administered with influenza H7N9 antigen HA1-2 in chickens, but also supports the use of PEI as a versatile systemic adjuvant platform in poultry.